2010
DOI: 10.1371/journal.pbio.1000453
|View full text |Cite
|
Sign up to set email alerts
|

MLL2 Is Required in Oocytes for Bulk Histone 3 Lysine 4 Trimethylation and Transcriptional Silencing

Abstract: Conditional knockout mouse strategies identify the histone methyltranferase MLL2 as a key player in epigenetic reprogramming of female gametes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(188 citation statements)
references
References 86 publications
8
178
2
Order By: Relevance
“…Collectively, we conclude that paternal H3K4me1 catalyzed by the Mll3/4 complex is required for minor ZGA in the paternal genome, and its alteration causes developmental arrest in 4-to 8-cell stage embryos, which is distinct from major ZGA phenotype (i.e., arrest in 2-to 4-cell stages) induced by a-amanitin treatment, or depletion of Mll2 or Brg-1 [23,35]. Interestingly, this delayed growth retardation may be explained by a "stepwise" gene activation model; that is, one transcriptional wave triggers the following transcriptional waves during preimplantation development, and thus, ZGA transcripts and their protein products would be required for the progression of embryos beyond the 4-cell stage [36].…”
Section: Embo Reportsmentioning
confidence: 78%
See 1 more Smart Citation
“…Collectively, we conclude that paternal H3K4me1 catalyzed by the Mll3/4 complex is required for minor ZGA in the paternal genome, and its alteration causes developmental arrest in 4-to 8-cell stage embryos, which is distinct from major ZGA phenotype (i.e., arrest in 2-to 4-cell stages) induced by a-amanitin treatment, or depletion of Mll2 or Brg-1 [23,35]. Interestingly, this delayed growth retardation may be explained by a "stepwise" gene activation model; that is, one transcriptional wave triggers the following transcriptional waves during preimplantation development, and thus, ZGA transcripts and their protein products would be required for the progression of embryos beyond the 4-cell stage [36].…”
Section: Embo Reportsmentioning
confidence: 78%
“…Previously, Mll2 was reported to be required for early embryogenesis, based on the observations of decreased H3K4me2/3 in maternal PNs concomitant with~30% reduction of major ZGA and developmental arrest mainly at 2-cell stages, when it was knocked out [23]. To determine the enzyme responsible for H3K4 methylation during minor ZGA, we first investigated their expression levels from MII oocytes to 2-cell stage embryos using the Database of Transcriptome in Mouse Early Embryos (DBTMEE, http://dbtmee.…”
Section: Mll3/4 Expression In the Pn Stage Is Necessary For Early Prementioning
confidence: 99%
“…It has indeed been suggested that these Histone modifications, called bivalent marks, can poise developmental genes until later activation or repression, during differentiation (Bernstein et al, 2006). Interestingly, oocytes lacking MLL2 -a methyltransferase responsible of H3K4 tri-methylation during oocyte growth-display a failure in global transcriptional silencing which is in opposition to its believed role of active mark (Andreu-Vieyra et al, 2010).…”
Section: Three Dimensional Localization Of Constitutive Heterochromatmentioning
confidence: 99%
“…In addition to roles for histone methylation associated with repressive chromatin, trimethylation of H3K4, an active mark, has also been shown to be important in the female germline. Oocytespecific deletion of Mll2, an H3K4 methyltransferase, results in decreased levels of H3K4 methylation in peri-ovulatory oocytes and impairs either ovulation or pre-implantation development, depending on the timing of conditional deletion during oogenesis [63].…”
Section: Dna Methylationmentioning
confidence: 99%